'Gamekeeper Turned Poacher': Frank Chapple, Anti-Communism, and Soviet Human Rights Violations. Issue 3 (1st December 2021) - Hurst, Mark
Abstract : The inclusion of the British trade union leader Frank Chapple on the panel of the 1985 Sakharov hearings, an event designed to hold the Soviet authorities to account for their violation of human rights, raises questions about the workings of the broader network of activists highlighting Soviet abuses. This article assesses Chapple's support for human rights in the Soviet Union, arguing that because of his historic membership of the Communist Party and subsequent anti-communist leadership of the Electrical Trades Union (ETU) in Britain, his support for victims of Soviet persecution was multifaceted in the Cold War context.